Pulmonary Hemodynamics, Cerebral Oxygenation, Intracranial and Perfusion Pressures in Pulmonary Complications in Victims with Severe Brain Injury - Yu. A. Churlyaev; V. Ya. Martynenkov; M. L. Sytin; L. Yu. Redkokasha; Yu. I. Mikhailovichev (Общая реаниматология, 2007)
Objective: to study pulmonary hemodynamics, cerebral oxygenation, intracranial and perfusion pressures in pulmonary complications in victims with severe brain injury (SBI). Subjects and materials. Retrospective studies were conducted in 47 victims with isolated brain injury. Of them, 30 patients made up a study group with poor prognosis (death, vegetative state, and severe disability). In the presence of negative clinical and neurological changes, they developed pneumonia, acute respiratory distress syndrome (ARDS) of different stages, ARDS concurrent with pneumonias. All the victims underwent invasive dynamic studies of pulmonary hemodynamics, intracranial pressure (ICP), by calculating cerebral perfusion pressure (CPP) and cerebral oxygenation (CO). Results. The studies have shown that pulmonary pressure, pulmonary vascular resistance, and pulmonary capillary wedge pressure increase and heart failure develops in the SBI victims with evolving pulmonary complications. Along with cardiopulomonary changes, ICP elevates and CPP and CO decrease. Conclusion. In traumatic brain lesions, it is very important to have information pertaining to the cardiopulmonary system and an estimation of ICP, CPP, and CO. Only comprehensive monitoring allows one to avoid the narrowness of evaluating the condition of a patient with SBI, to timely detect the development of secondary brain lesions, and to control the efficiency of intensive care. Key words: severe brain injury, pulmonary hemodynamics, intracranial and cerebral perfusion pressures, cerebral oxygenation.